Evaluating Teacher Training and Professional Development in the New Education Policy (NEP) 2020 - Jajal Ila Natavarlal (Vidhyayana - An International Multidisciplinary Peer-Reviewed E-Journal - ISSN 2454-8596, 2023)
Introducing the National Curriculum Framework for Teacher Education (NCFTE), focusing on 21st-century skills and competencies, is a pivotal step in reshaping education in India. This framework emphasizes the critical role of educators in fostering these skills and competencies in students. Mandatory Continuous Professional Development (CPD) of 50 hours annually for teachers ensures that they stay updated with best practices and adapt to changing pedagogical landscapes. Revamping teacher recruitment with live teacher demonstrations and re-evaluating Teacher Eligibility Tests (TETs) material aims to bring in highly qualified individuals who can meet diverse student needs. Financial incentives for higher education and professional development further empower educators to provide enriched learning experiences. However, challenges such as the shortage of qualified teacher educators, unequal access to CPD resources, and the need to shift mindsets towards professional development must be addressed. The National Education Policy (NEP) 2020 has the potential to significantly elevate teacher training and professional development in India, ensuring students have equitable access to high-quality education facilitated by well-prepared, continuously evolving educators.